Fabrication, Characterization, and Hemocompatibility Investigation of Polysulfone Grafted With Polyethylene Glycol and Heparin Used in Membrane Oxygenators. Issue 11 (November 2016) - Zheng, Zhi; Wang, Weiping; Huang, Xin; Lv, Quan; Fan, Wenling; Yu, Wenkui; Li, Lei; Zhang, Zhibing
Abstract: Polysulfone (PSF) was grafted chemically with polyethylene glycol (PEG) of different molecular weights (400, 2000, 10 000, and 20 000) and heparin to prepare PSF–PEG–Hep membranes (labeled as PSF–PEG400–Hep, PSF–PEG2000–Hep, PSF–PEG10 000–Hep, and PSF–PEG20 000–Hep). These membranes were synthesized via the following steps: (i) PSF chloromethylation; (ii) PEGylation; and (iii) heparin immobilization process. Water contact angle, critical water permeation pressure, ATR–FTIR, 1 H NMR, UV–visible spectrophotometry, and X‐ray photoelectron spectroscopy were conducted to prove grafting success and to fix the optimal reaction parameters during chemical modification processes. To further evaluate the application potential of the PSF–PEG–Hep membrane in a membrane oxygenator, we conducted pure CO2 and O2 gas permeation tests and measured the gas exchange rates of CO2 and O2 through a membrane oxygenator using fresh porcine blood. Meanwhile, the hemocompatibility of the membrane was analyzed and compared by protein adsorption, platelet adhesion, and blood coagulation tests. Results of pure gas permeation experiments indicated that the excellent gas transmission properties through PSF membrane were preserved after modification. Blood oxygenation experiments through the PSF–PEG10 000–Hep membrane showed that when the flow rate of porcine blood was 1.5 L/min, CO2 and O2 exchange rates reached 102 and 110 mL/min, respectively, which could basically satisfy the gas exchange potential of commercial membrane oxygenators. Besides, the PSF–PEG–Hep membrane has demonstrated more prominent blood compatibility than PSF.